THE ROLE OF TECHNOLOGY ON BUSINESS STRATEGY PERFORMANCE IN BUILDING CORE COMPETENCE IN SMALL MEDIUM ENTERPRISES MOGADISHU - SOMALIA. - AHMED, ABDINOR ABUKAR (Advances in Social Sciences Research Journal, 2022)
The goal of this research was to look at the effect of technology on business strategy performance in Mogadishu, Somalia. The study focused on the impact of communication technologies on business strategy performance in Mogadishu, Somalia, the impact of digital marketing technologies on business strategy performance in Mogadishu, Somalia, and the significance of business information management technologies on business strategy performance in Mogadishu, Somalia. This study was conducted among a pre-selected group of local small and medium-sized enterprises (SME). The intended audience consisted of business employees and general managers. Staff and general managers were chosen based on their knowledge and expertise in the roles of technology in the attainment of business goals in their respective regions. The study's sample size was 92 respondents from the target population. This is due to the nature of the data to be created, which involves the employment of numerous methodologies to gain a better knowledge of the study issue under consideration. According to Amin, the method is also well-known for enhancing validity and reliability while decreasing biases (2012). Sloven's algorithm was used to estimate the sample size of genuine respondents. To collect data, self-administered questionnaires were used, and these were sent to employees and general managers for replies. This study found that communication technologies have a significant impact on the success of business strategies at small and medium-sized enterprises (SMEs) in Mogadishu, Somalia, although digital marketing and business information management technologies had a minor impact. Business strategy and technology are tightly connected. A business strategy cannot be implemented if a firm lacks technology. Even firms that have successfully linked business and technology strategies fail to recognize the l ink between effective intellectual capital strategy and both business and technology strategies, so the researcher advised companies to focus on technology as a core competence and continue to b enefit from its various strategies such as communication strategies and digital marketing strategie s.